New Scale-insects (Homoptera Coccoidea) for the Italian fauna collected in the Veneto region (Bollettino di zoologia agraria e bachicoltura, 2024)
The paper deals with the presence in Italy of six species of Homoptera Coccoidea, new for the Italian fauna, collected in the Veneto region. They are: Chnaurococcus danzigae Kozar & Kosztarab, Euripersia europaea (Newstead), Peliococcopsis caucasicus (Borchsenius), Phenacoccus evelinae (Tereznikova), Phenacoccus interruptus Green (Fam. Pseudococcidae), Parafairmaria gracilis Green (Fam. Coccidae). Records on host plants, localities and distribution of the above mentioned species are given. Two other species of Phenacoccus collected in the same region, Phenacoccus sp. and P. avenae Borchsenius? need of a deeper study to clarify their identity.
Keywords: Scale-insects; new records; Italy